Nelson Rodrigues' memories: Connecting Elements between Journalism and Drama - da Silva, José Francisco Quaresma Soares; Panichi, Edina Regina Pugas [UNESP] (Universidade Estadual de Londrina, 2018)
Abstract: In 1967, Nelson Rodrigues debuts at the column Memórias in the newspaper Correio da Manhã. The writer acknowledge the space of the newspaper as a laboratory for the construction of several of his dramatic texts. The aim of this work is to highlight and analyze his experiences as forming elements of the journalist's authorial personality, a material that reverberates in the constitution of the narrative texts and fits in the construction of his dramatic work.
Memórias de Nelson Rodrigues: Elementos Conectores entre Jornalismo e Dramaturgia
Keywords: Dramaturgy; Journalism; Memories; Narrative